2014
DOI: 10.1159/000362837
|View full text |Cite
|
Sign up to set email alerts
|

Using Gene Expression to Improve the Power of Genome-Wide Association Analysis

Abstract: Background/Aims: Genome-wide association (GWA) studies have reported susceptible regions in the human genome for many common diseases and traits; however, these loci only explain a minority of trait heritability. To boost the power of a GWA study, substantial research endeavors have been focused on integrating other available genomic information in the analysis. Advances in high through-put technologies have generated a wealth of genomic data and made combining SNP and gene expression data become feasible. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
(54 reference statements)
2
7
0
Order By: Relevance
“…In other words, PrediXcan and TWAS put a higher weight on an SNP (eSNP) that is more strongly associated with the gene's expression level, in agreement with empirical evidence that eSNPs are more likely to be associated with complex traits and diseases (Nicolae et al 2010). This new formulation also points out the connection to existing weighted association analysis (Roeder et al 2006;Ho et al 2014). More importantly, since the same association test in PrediXcan and TWAS suffers from power loss under some common situations, we develop an alternative and more powerful association test with broader applications.…”
supporting
confidence: 77%
“…In other words, PrediXcan and TWAS put a higher weight on an SNP (eSNP) that is more strongly associated with the gene's expression level, in agreement with empirical evidence that eSNPs are more likely to be associated with complex traits and diseases (Nicolae et al 2010). This new formulation also points out the connection to existing weighted association analysis (Roeder et al 2006;Ho et al 2014). More importantly, since the same association test in PrediXcan and TWAS suffers from power loss under some common situations, we develop an alternative and more powerful association test with broader applications.…”
supporting
confidence: 77%
“…This weight-adjustment approach is expected to boost the power of association analysis by incorporating additional genomic information while keeping the FWER controlled at a nominal level. Both simulation studies and experimental findings reported in Li et al [7] and Ho et al [8] support the expected gain in power through the weight-adjustment procedure.…”
Section: Discussionsupporting
confidence: 67%
“…It is also modifiable for when SNP , gene expression data and gene expression, phenotype data are from two different sets of cohorts, instead of paired gene expression and GWAS data from the same cohort. However, paired gene expression and GWAS data from the same cohort might be preferable, as the data will have increased power to detect the causative relationship (SNP→E→P) but not the reactive relationship (SNP→P→E) based on the simulation study described in [8]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation studies have suggested that incorporating together such rich data can lead to substantial gain in statistical power. This integrative approach was applied successfully to find susceptibility variants in genes associated with blood pressure regulation [78,102]. Furthermore, a number of studies have successfully used similar methods to integrate GWAS data with biological networks data (protein-protein interaction and coexpression networks) to predict causal genes at associated GWAS loci for various disorders [103][104][105][106].…”
Section: Alternate Methodsmentioning
confidence: 99%